2008
DOI: 10.1186/bcr2131
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment with anti-cytokeratin alone or combined with anti-EpCAM antibodies significantly increases the sensitivity for circulating tumor cell detection in metastatic breast cancer patients

Abstract: Introduction Circulating tumor cells (CTCs) are detectable in most cancer patients and they can meet an existing medical need to monitor cancer patients during a course of treatment and to help determine recurrent disease. CTCs are rarely found in the blood of cancer patients and enrichment is necessary for sensitive CTC detection. Most CTC enrichment technologies are anti-EpCAM antibody based even though CTC identification criteria are cytokeratin positive (CK + ), CD45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(125 citation statements)
references
References 49 publications
4
118
0
3
Order By: Relevance
“…Several authors reported the heterogeneous expression of EpCAM in mammary carcinomas (Thurm et al, 2003) and downregulation of EpCAM has been reported for disseminated tumour cells in bone marrow and CTCs in peripheral blood (Thurm et al, 2003;Rao et al, 2005). Recently, Deng et al (2008) showed that CTC enrichment with anti-cytokeratin antibodies, in combination with anti-EpCAM antibodies, significantly enhances assay sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the heterogeneous expression of EpCAM in mammary carcinomas (Thurm et al, 2003) and downregulation of EpCAM has been reported for disseminated tumour cells in bone marrow and CTCs in peripheral blood (Thurm et al, 2003;Rao et al, 2005). Recently, Deng et al (2008) showed that CTC enrichment with anti-cytokeratin antibodies, in combination with anti-EpCAM antibodies, significantly enhances assay sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several slide-based automated microscopic scanning devices, such as the Ikoniscope® [17] and the Ariol® system [18,19], have been applied for standardized micrometastatic cell detection and characteri zation. Another approach has been developed that uses fi ber-optic array scanning technology (FAST) for rare cell detection [20].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Another system for CTC detection is the so-called Ariol system, which is based on image capturing. Three fluorescent images of cell surface antigens like CK or EpCAM and one brightfield image of one cell are taken together for detection of tumour cells (72). Flow cytometry can also be used for CTC detection, with the advantage, that multiple cell parameters, such as DNA-content, cell size and cellular markers can be analysed simultaneously and has thereby advanced to be a specific method to monitor breast cancer patients receiving chemotherapy (73).…”
Section: Ctc Detectionmentioning
confidence: 99%